The effects of an 8-week functional training program on functional movement and physical fitness in male university students: a randomized controlled trial - Li, Lingwei; Meng, Fanyi; Yao, Siqi; Shi, Qingfu; Luo, Chao (Frontiers in Public Health, 2025)
ObjectiveThe physical fitness and functional movement capabilities of university students are fundamental to their long-term health, yet traditional physical education models may have limitations in concurrently enhancing both aspects. This study aimed to compare the effects of an 8-week functional training (FT) program versus a traditional training (TT) program on functional movement quality and comprehensive physical fitness in non-athlete male university students.MethodsThis study was a randomized controlled trial. Thirty-five healthy male university students (mean age 18.8 ± 0.9 years) were randomly assigned to either a functional training group (FT group; n = 20) or a traditional training group (TT group; n = 20). During the 8-week intervention, the FT group performed exercises centered on integrated, multi-joint, multi-planar movements. The TT group engaged in a traditional physical education program of matched duration and frequency, which focused on isolated fitness exercises and basic sports skills. Assessments were conducted at baseline (week 0), mid-intervention (week 4), and post-intervention (week 8). Main outcome measures included scores for the seven components of the Functional Movement Screen (FMS) and five physical fitness indicators (50-m sprint, 1,000-m run, sit-and-reach, standing long jump, and vital capacity).ResultsSignificant time × group interaction effects were observed for most outcome measures. Compared to the TT group, the FT group demonstrated significantly greater improvements in the total FMS score and several components, particularly those assessing dynamic stability and core control (e.g., Active Straight-Leg Raise, Rotary Stability; p < 0.01). Furthermore, the FT group showed superior gains across all five physical fitness indicators, including speed, endurance, flexibility, power, and vital capacity (all interaction effects, p < 0.05).ConclusionFor male university students, an 8-week functional training program is more effective than a traditional training regimen for concurrently improving functional movement patterns and comprehensive physical fitness. These findings support the integration of functional training principles and methods into university physical education curricula to more effectively enhance students’ overall physical preparedness and movement quality.